2004
DOI: 10.1093/bioinformatics/bti038
|View full text |Cite
|
Sign up to set email alerts
|

Expression-based monitoring of transcription factor activity: the TELiS database

Abstract: In two validation studies, TELiS accurately detected in vivo activation of NF-kappaB and the Type I interferon system by HIV-1 infection and pharmacologic activation of the glucocorticoid receptor in peripheral blood mononuclear cells. The population-based statistical inference underlying TELiS out-performed conventional statistical tests in analytic sensitivity, with parametric studies demonstrating accurate identification of transcription factor activity from as few as 20 differentially expressed genes. TELi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
194
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 39 publications
2
194
0
Order By: Relevance
“…TELiS analyzes differential gene expression data in terms of the prevalence of transcription factorbinding motifs (TFBMs) within the promoters of differentially expressed genes. This approach can accurately identify the activation of specific hormone or cytokine signaling pathways based on the resulting pattern of gene induction which occurs selectively in genes bearing TFBMs responsive to transcription factors activated through that pathway (23). The present analyses assessed glucocorticoid receptor activity using the TRANSFAC V$GR_Q6 DNA motif, and NF-κB/Rel transcription factor activity using the V$CREL_01 motif (which was characterized by binding of the p50/p65 cRel heterodimer, but can also bind RelB and other NF-κB/Rel family proteins; 33).…”
Section: Monocyte Gene Expressionmentioning
confidence: 99%
“…TELiS analyzes differential gene expression data in terms of the prevalence of transcription factorbinding motifs (TFBMs) within the promoters of differentially expressed genes. This approach can accurately identify the activation of specific hormone or cytokine signaling pathways based on the resulting pattern of gene induction which occurs selectively in genes bearing TFBMs responsive to transcription factors activated through that pathway (23). The present analyses assessed glucocorticoid receptor activity using the TRANSFAC V$GR_Q6 DNA motif, and NF-κB/Rel transcription factor activity using the V$CREL_01 motif (which was characterized by binding of the p50/p65 cRel heterodimer, but can also bind RelB and other NF-κB/Rel family proteins; 33).…”
Section: Monocyte Gene Expressionmentioning
confidence: 99%
“…Total RNA was extracted and treated with RNAse-free DNAse (Qiagen) following the manufacturer's protocol (supplemented by one additional wash in RW1 reagent and one additional wash in RPE reagent to remove excess salt). RNA purity and integrity were assessed using an Agilent 2100 bioanalyzer (Agilent Technologies, Santa Clara CA), and genome-wide transcription profiling was carried out using Affymetrix U133A high density oligonucleotide arrays (Affymetrix, Santa Clara CA) in the UCLA DNA Microarray Core, as previously described (Cole, Galic et al 2003;Cole, Yan et al 2005). Low level gene expression was quantified by Robust Multiarray Averaging (Bolstad, Irizarry et al 2003), and differentially expressed genes were identified by a ≥ 2-fold difference in mean expression level (corresponding to a 5% False Discovery Rate) (Benjamini and Hochberg 1995;Cole, Galic et al 2003) in paired comparisons of grade-and stage-matched pairs of tumors from high vs. low biobehavioral risk patients.…”
Section: Tumor Tissue Gene Expressionmentioning
confidence: 99%
“…The primary hypothesis regarding CREB/ATF transcription factors and secondary hypotheses regarding NF-κB/Rel and Ets family transcription factors were tested using a 2-sample variant of the Transcription Element Listening System (TELiS) (Cole 2005;Cole, Yan et al 2005). TELiS contains data on the prevalence of 192 vertebrate transcription factor-binding motifs (TFBMs) from the TRANSFAC database (Wingender, Dietze et al 1996) in the promoters of all genes assayed by the Affymetrix U133A high-density oligonucleotide array.…”
Section: Transcription Control Pathway Analysismentioning
confidence: 99%
See 2 more Smart Citations